(3eaGgje eYGUQIs - (3fXGe ehSi(B, (3ShjOGfs ((3YeGf(B:s (3OGQ GdMGeO ddfTQ hGdJhRjY(B,s, 2006)
(3ebOeI YGeI aj GdJShjb(B- (3GdHjFI GdJShjbjI(B- (3GdeSDhdjI GdELJeGYjI hGdCNdGbjI ddJShjb(B- (3HMhK GdJShjb hCfXeI GdeYdheGJ GdJShjbjI(B- (3JLRFI GdShb(B- (3Sdhc GdeSJgdc GdTQGFj(B- (3Sdhc efXeGJ GdCYeGd GdTQGFj(B- (3GSJQGJjLjI GdJSYjQ(B- (3GSJQGJjLjI GdJhRjY(B- (3GSJQGJjLjI GdJQhjL(B- (3GdJShjb GdOhdj(B- (3GdJShjb GdEdcJQhfjs
Keywords: (3EOGQI GdCYeGds; (3GdHjFI GdJShjbjIs; (3GdJShjbs